Epidemiological pattern of injuries among road traffic crash victims: the first experience of a large tertiary care hospital in the West Bank of Palestine - Alaa H. Rostom; Duha Suboh; Tasneem Dweikat; Inam Hindi; Zain Farounyeh; Ramzi Shawahna (BMC Emergency Medicine)
Abstract Background Road traffic injuries are a global public health challenge. This study was conducted to describe the epidemiological patterns of road traffic injuries in a large tertiary care hospital in the West Bank of Palestine. In addition, associations between the different variables of the victims and the patterns of road traffic injuries were also assessed. Methods This study was conducted in a retrospective cohort observational design between January 2021 and July 2023 at a large tertiary care hospital in Nablus, Palestine. The data were collected from the electronic medical record system of the large tertiary care hospital using a data collection form. Results A total of 1,544 victims of traffic road injuries were included in this study. Lower limb (43.0%), neck (41.2), and upper limb (39.8%) injuries were the most common types of road traffic injuries sustained by the victims admitted to the large tertiary care hospital. The victims who were 30 years or older were more likely to sustain back injuries (aOR = 1.71, 95% CI: 1.20–2.45) pelvic injuries (aOR = 1.84, 95% CI: 1.08–3.12), chest injuries (aOR = 1.59, 95% CI: 1.06–2.38), and neck injuries (aOR = 2.54, 95% CI: 1.68–3.82) compared to the victims who were younger than 30 years. The victims who did not use seatbelts were more likely to sustain abdominal injuries (aOR = 1.88, 95% CI: 1.34–2.63) and head injuries (aOR = 1.49, 95% CI: 1.06–2.10) compared to the victims who used seatbelts. The victims who did not have the airbag deployed were more likely (aOR = 1.85, 95% CI: 1.31–2.63) to sustain neck injuries compared to the victims who had the airbag deployed. Conclusion The epidemiological patterns of road traffic injuries in a large tertiary care hospital in Nablus, Palestine were described and the associations between the different variables of the victims and the patterns of road traffic injuries were assessed. The findings indicated a need to design measures to prevent/minimize these injuries. Future studies are still needed to determine the best measures to avoid/minimize the incidence of serious road traffic injuries.